Proverb: Nearly Spring in a New Hampshire Barn - Randall, Regine (On and Off the Road: Poems of New Hampshire, 2020)
"This poetry anthology, with poems from poets throughout New England and from other states - is a result of Peterborough Poetry Project's second poetry contest. We invited poets, writers, and observers to submit up to three poems about New Hampshire - past, present, future, or fantasy. Forty-eight poems from the contest form this book. The poems are in three different sections by themes: People, Places, and The Wild, but readers may find that several poems have more than one theme. A poem may appear to be about nature, but also our reactions to it. Another poem may appear to be true, but might be pure fantasy. Such is the nature of poetry: read it for the obvious, then read it again to see if more reveals itself"–Back cover
Google-Books-ID: 9QSYzQEACAAJ
Keywords: dept.cur; literary-poetry